Effects of testosterone and corticosterone on somal size and dendritic spine density of posterodorsal medial amygdala neurons in male rats. - Budi Perwira, Andre. (2011)
Increased level of testosterone is responsible for sexual characteristic changes during puberty, and the activation of sexual behaviors in adults. Posterodorsal subnucleus of medial amygdala (MeApd) of the brain, which has numerous androgen receptors and estrogen receptors, is important in the expression of sexual behavior as indicated by previous blocking studies. Higher and lower level of testosterone increases and reduces respectively MeApd soma size, regional volume, and dendritic connections as shown in the castration and testosterone resupplementation experiments. Upregulation of corticosterone downregulates testosterone production. Stress induces higher level secretion of corticosterone, and this in turn induces dendritic expansion in basolateral amygdala as shown in both acute and chronic vehicle treatment done recently by Mitra and Sapolsky. Effects of testosterone and corticosterone on MeApd morphology were characterised. Male Wistar rats, divided into control, testosterone treatment, and corticosterone treatment, were sacrificed after 10 days of single injection to see the effects of both hormones in the morphology of MeApd. As expected we showed that single high dose of testosterone were sufficient to significantly increase the soma size and the number of dendritic spines in MeApd, whereas surprisingly corticosterone had no effect on soma size but increased the dendritic density of MeApd.